2007
DOI: 10.1029/2006wr005379
|View full text |Cite
|
Sign up to set email alerts
|

Impact of coating development on the hydraulic and transport properties in argillaceous limestone fracture

Abstract: [1] Results are reported for an acidic water flow-through experiment conducted in a fractured argillaceous limestone sample (73% carbonates). The change in fracture geometry and related parameters is reported for six data sets obtained from synchrotron X-ray microtomography experiments. High-resolution three-dimensional images of the sample allowed quantification of the changes in fracture morphology at a spatial resolution of 6 mm. Mineral mass loss and permeability changes in the sample were also determined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
212
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(223 citation statements)
references
References 55 publications
(60 reference statements)
11
212
0
Order By: Relevance
“…Moreover, a self-healing mechanism that prevents CO 2 leakage has been observed in argillaceous limestones (88). We conjecture that these mechanisms, together with increased buoyancy, may explain why CO 2 natural analogs often leak at shallow depths (less than 700 m, where CO 2 is gaseous), but deep natural CO 2 deposits rarely do (89).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, a self-healing mechanism that prevents CO 2 leakage has been observed in argillaceous limestones (88). We conjecture that these mechanisms, together with increased buoyancy, may explain why CO 2 natural analogs often leak at shallow depths (less than 700 m, where CO 2 is gaseous), but deep natural CO 2 deposits rarely do (89).…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, re-activation of micro cracks plays an important role in the flow of CO 2 (Angeli et al, 2009). Ellis et al (2011a,b) observed that the low content of clay minerals, compared with those in samples used by Noiriel et al (2007), Andreani et al (2008) and Angeli et al (2009), prevents the formation of a continuous clay coating along the fracture. Moreover, local heterogeneity exerts strong control over the location of preferential pathways at the microscale (Smith et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Research into the interaction between the caprock and CO 2 -rich brine through potential leakage pathways is of paramount importance in order to evaluate caprock sealing capacity (Kaszuba et al, 2005;Noiriel et al, 2007;Andreani et al, 2008;Busch et al, 2008;Hangx et al, 2010;Ellis et al, 2011a,b;Berrezueta et al, 2013;Smith et al, 2013). Acidified CO 2 -rich brines may react with caprock minerals that are susceptible to dissolution, releasing ions into the solution that could lead to mineral precipitation (Knauss et al, 1993;Brady and Carroll, 1994;Pokrovsky et al, 2009;Hellmann et al, 2010;Smith and Carroll, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past two decades, X-ray computed tomography (xCT) has become a valuable tool for 3D visualization and characterization of geological specimens [1][2][3][4][5][6][7][8][9], including fracture geometries [10][11][12][13][14][15][16][17][18][19][20][21], pore networks [22][23][24][25][26][27][28][29][30][31], crystal sizes [32,33], and mineral phases [3,[34][35][36][37][38][39]. xCT imaging is indispensable for non-destructive observation of geometry of fractures, which is important because fractures provide preferential flow conduits and often dominate mass transfer in geological materials.…”
Section: Introductionmentioning
confidence: 99%